A Patient as Art: Andrew Wyeth's Portrayal of Christina Olson's Neurologic Disorder in Christina's World. (June 2017) - Patterson, Marc C.; Cole, Thomas B.; Siegel, Eliot; Mackowiak, Philip A.
In Christina's World, one of the most beloved works of American art, Andrew Wyeth painted Christina Olson crawling crablike across the field below her house, raised on emaciated arms, with a swollen knob for an elbow, and hands clenched and gnarled. The significance of these physical abnormalities, and the message Wyeth endeavored to convey via the portrait, are considered here in light of Christina's medical history and the disorder it most likely signifies.